2010
DOI: 10.1111/j.1526-4610.2009.01520.x
|View full text |Cite
|
Sign up to set email alerts
|

Endonasal Endoscopic Management of Contact Point Headache and Diagnostic Criteria

Abstract: Surgery in specific cases of headaches with more positive evidence of contact point could be successful, particularly if medical therapy has failed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
20
0
2

Year Published

2011
2011
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 14 publications
1
20
0
2
Order By: Relevance
“…In spite of the low level of evidence, selected patients with mucosal contact points who appear to benefit from directed nasal surgery are those who have failed medical therapy for migraine and tension‐type headache, have otherwise normal endoscopy and CT scan, and have symptomatic improvement with local anesthetic application to the contact point in preoperative evaluation . However, it is not clear why a significant proportion of patients have residual symptoms after surgery . In addition, several studies claimed good response to surgical treatment in patients with less strict selection criteria.…”
Section: Discussionmentioning
confidence: 99%
“…In spite of the low level of evidence, selected patients with mucosal contact points who appear to benefit from directed nasal surgery are those who have failed medical therapy for migraine and tension‐type headache, have otherwise normal endoscopy and CT scan, and have symptomatic improvement with local anesthetic application to the contact point in preoperative evaluation . However, it is not clear why a significant proportion of patients have residual symptoms after surgery . In addition, several studies claimed good response to surgical treatment in patients with less strict selection criteria.…”
Section: Discussionmentioning
confidence: 99%
“…In the study of Mohebbi et al on 36 patients with chronic headaches who had not previously responded to conventional treatments, the intensity of the headaches, pre-and post-operatively, were compared by utilizing the VAS. 7 The overall success rate approximated 83% after surgery. Also, Mariotti et al revealed that, endoscopic sinus surgery in rhinogenic headache was widely successful on their patients, and 28 (84.8%) of 33 patients had reported an improvement.…”
Section: Discussionmentioning
confidence: 99%
“…2,3 This, these investigators suggest, may support a role for contact point surgery even in patients with underlying migraine. 4,5 Rhinogenic Headache Rhinogenic headaches are those with primary pathophysiology in the nose with facial or structural head pain, and should be considered as secondary headaches. Acute rhinosinusitis and chronic or recurring rhinosinusitis both may cause headache.…”
Section: Anatomy Of Facial Painmentioning
confidence: 99%